Classification of wild tomatoes: a review - Peralta, Iris Edith (2000)
Wild tomatoes are native to western South America. The generic status of wild tomatoes within the Solanaceae has been controversial since the eighteen century. Linnaeus in 1753 placed tomatoes in Solanum while Miller, a contemporary of Linnaeus, classified tomatoes in a new genus. The majority of later botanists have followed Miller. Differing numbers of species and conflicting supraspecific classifications have been proposed, based on morphology or crossing studies. Two major crossability groups have been identified, one that includes mainly self-compatible species that easily cross with the cultivated tomato, and another that comprises self-incompatible species not easily cross with the cultivated tomato. Recent molecular investigations using appropriate outgroups have shown that tomatoes and potatoes are close related phylogenetically, and support the inclusion of tomatoes within Solanum, the classification advocated here. We discuss the conflicting goals of classifications based on predictivity versus stability, a continuing controversy in systematics.